Agricultural Geography Analysis of Carob Tree (Ceratonia siliqua L.) from Turkey - (:unkn) unknown (My University, 2016)
0

Carob tree (Ceratonia siliqua L.) is one of the oldest trees in the world and has been cultivated from civilization of Ancient Persia, especially on the Mediterranean coasts, till nowadays. The fruit of the carob tree (carob bean) are attracting attention in recent years due among others to tits rich nutritional value and use as a substitute and/or alternative for cocoa. Although it has higher sugar content than sugar beet and sugar cane, it is a food that also lowers cholesterol. In addition to its fruit, the plant has interesting morphological qualities. Deep root system of carob tree allows high productivity even in draught conditions; it is an ideal plant in the fight against erosion and one of the most preferred plants while establishing fire-resistant forests. Additionally, because 2016 was declared the International Year of Pulses, it is necessary to draw attention to the carob tree since it is a typical pulse plant. The status of Turkey, as the 5th carob producer in the world, was analysed in this context, in terms of Agricultural Geography. The existing and necessary practices in carob production are discussed based on the data from the studies conducted in Antalya and Mersin in 2015 and previous ones.
Keywords: Ziraat Mühendisliği; Gıda Bilimi ve Teknolojisi